İstanbul Halveti Tekkeleri - Köse, Fatih (My University, 2010)
Bu tezin amacı İstanbul’da kurulan Halvetî tekkelerini tesbit edip, tarihsel açıdan incelemektir. Öncelikle tezin giriş bölümünde Halvetîlik ve tekke müessesesi hakkında bilgiler verilmiştir. Birinci bölümde kuruluşundan sonuna kadar Halvetîliğe bağlı olarak hizmet veren 72 tekke kronolojik olarak ele alınmıştır. İkinci bölümde ise belli bir dönem Halvetîliğe bağlı bulunan 52 tekke yine kronolojik olarak incelenmiştir. Tekkeler incelenirken öncelikle ne zaman kurulduğu, İstanbul’daki yerleri, geçirdiği tamirler, tekkenin tarihi özellikleri, tekkede görev alan postnişinler hakkında bilgiler verilmiştir. Tezin ekler bölümünde söz konusu tekkelerin yerleri haritalar üzerinde gösterilmiştir. Ayrıca tekkelerin eski ve yeni fotoğraflarına yer verilmiştir.

This study purports to detect and examine the Khalwati Dervish Lodges in İstanbul with respect of their historical impotance. Especially, the first part of the thesis is dedicated to the Dervish Lodges and Khalwatism. Within the framework of the first part, seventy two Dervish Lodges, that served with Khalwati ideology from the very start to their end, are examined in compliance with the historical order. Within the second part fifty two Dervish Lodges, that once served the Khalwatism, were examined in their historical order. While examining these Dervish Lodges, there we provided their dates of establishmet,their locations, the repairs made to them, historical features of them and the Sheikhs who worked there. Within the annexes the location of the Dervish Lodges are shown on the maps and the old and new photos of the Dervish Lodges are given.
Keywords: İslam Tarihi; İstanbul_İslam Tarihi; Tekkeler